Understanding the Socio-Economic and Hygienic Status of Child Labourers in Nepal - Joshi, Sunil Kumar; Shrestha, S; Shrestha, R; Vaidya, S (Nepal Journal of Epidemiology, 2011)
Background The International Labour Organization (ILO) defines child labour as “work that deprives children of their childhood, their potential and their dignity, and that is harmful to physical and mental development. The ILO has estimated that in 2004, almost 218 million children (almost 1 in 7) aged 5-17 were involved in child labour worldwide, about 126 million under hazardous conditions. In Asian-Pacific region, 122 million children aged 5-14 were working as child labourers. It is imperative to know why the children are engaged in labour and what kind of effect child labour has in their health, education as well as the economy of their family. Methods This is a descriptive study which interviewed 313 child labourers working in different industries. It specially tried to assess the reasons why children joined the labour force, their family demographics, education and their general hygienic condition. Results 83.4% of child labourers joined labour because of poverty, 36.1% of them earned less than thousand rupees a month. 23.6% of them come from a big family with more than eight members. 30% (94) of them have not received even the primary level of education. Their overall hygienic condition is not satisfactory. Conclusion In Nepal, poverty is the most common cause of child labour and child labourers do not have a good hygienic condition. Key words: Child labour; Poverty; Earnings; Hygiene pressure DOI: http://dx.doi.org/10.3126/nje.v1i3.5573 Nepal Journal of Epidemiology 2011;1(3) 90-94